Influence of Individual Competence And Internal Control System On The Financial Management Performance of The Blu Batara Guru Hospital Luwu Regency - safitri m.djalle, dewi; Adi Patra, A. Dahri; Syamsuddin, Sofyan (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine the effect of individual competence and internal control systems on the financial management performance of BLU Batara Guru General Hospital in Luwu Regency. Methodology: This research adopts a quantitative approach using primary and secondary data collected through structured questionnaires. The sample consists of 79 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS version 21. Results: The findings indicate that individual competence has a positive and significant effect on financial management performance. Likewise, the internal control system significantly influences the financial management performance of the BLU hospital. Novelty: This study integrates human resource competence and internal control mechanisms as key determinants of financial management performance within a public service hospital context. Findings: Effective financial management performance is achieved when competent individuals are supported by a well-functioning internal control system. Originality: The originality of this research lies in its empirical evidence from a regional BLU hospital, providing insights into financial governance in the Indonesian public health sector. Conclusions: Improving employee competence and strengthening internal control systems are essential strategies to enhance accountable, transparent, and efficient financial management performance. Type of Paper: Empirical Research Paper.